9: ADAPTATION OF PREGNANCY RISK ASSESSMENT MONITORING SYSTEM (PRAMS) AND PROVIDE A MODEL ON IT. (8th February 2017) - Kharaghani, Roghieh; Shariati, Mohammad; Keramat, Afsaneh; Yunesian, Masud; Moghisi, Alireza
Abstract : Background and aims: A surveillance system helps to detect epidemics and the pattern of the problems incidence in the community and it is essential part of evidence based decision making process. This study aimed to adapt of PRAMS and provide a model on it. Methods: This study was performed in 7 steps as follows: Surveillance systems in pregnancy were reviewed and appropriate system was selected for Iran by nominal group technique. Two comparative studies were conducted to determine the similarities and differences between Iran and the selected community. PRAMS method and system were adapted based on the results of the comparative studies and experts opinions. The study tool was adapted. A field trial was conducted to assess adapted PRAMS feasibility based on TELOS (technical, economic, legal, operational, and schedule) model in the city of Shahriar, located in the west of Tehran, and to compare data collection methods. Then, based on the results and consultation with related executive managers, the final model of PRAMS was suggested for Iranian health system. Results: Review of the surveillance systems in pregnancy, identified six models. The results of the nominal group technique showed that, the appropriate model for Iran is PRAMS. Based on the comparative studies and expert opinions, the appropriate system and method for program was as follows: the sampling frame was composed of data in thyroid screening forms and hospital records, the sampling method was systematic, data collection methods were home and phone based surveys, and participants were women within 2 to 6 months postpartum who had a live or still birth. The study tool was adapted. Thirty-seven health volunteers collected the data in this study (technical feasibility). Any home based completed questionnaire cost 2.45 and a phone cost 1.89 USD. Many indices were achieved from the study, which were worth much more than the expenses (economic feasibility). The project was consistent with legal requirements (legal feasibility). There was no statistically significant differences in mother's participation rate between phone (90.9%) and home visit (92.8%) groups and about 90.8% of different sections of the questionnaire were completed (operational feasibility). All data collection processes took 35 days (schedule feasibility). Based on the study results, the appropriate model of surveillance system was suggested with the goals of reducing infant morbidity and mortality and promoting maternal health by influencing maternal and child health programs, and maternal behaviors during pregnancy and early infancy. Conclusion: The adapted PRAMS could be considered feasible in Iran and may offer a potential solution to some data deficits in maternal and child health indicators. Moreover, by monitoring pregnancy risks and outcomes, we can assess, analyses, and modify the current prenatal care program through PRAMS widespread and periodic implementation.